2005
DOI: 10.1111/j.1399-6576.2005.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability of duration of action of neuromuscular‐blocking drugs in elderly patients

Abstract: When used with sevoflurane/N(2)O, there was a two-fold greater variability of duration of neuromuscular blockade in elderly patients receiving rocuronium or vecuronium compared with cisatracurium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
58
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 19 publications
4
58
0
3
Order By: Relevance
“…Throughout onset of non-depolarizing block, T 4 disappears at about 75% depression of T 1 , T 3 at 80-85% depression of T 1 , and T 2 at 90% depression. During recovery from non-depolarizing block: T 1 appears again, first followed by T 2 , T 3 , and finally T 4 (4). .…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Throughout onset of non-depolarizing block, T 4 disappears at about 75% depression of T 1 , T 3 at 80-85% depression of T 1 , and T 2 at 90% depression. During recovery from non-depolarizing block: T 1 appears again, first followed by T 2 , T 3 , and finally T 4 (4). .…”
mentioning
confidence: 97%
“…A number of studies have indicated that the prevalance of postoperative residual curarization (PORC) increases with age (2,3).…”
mentioning
confidence: 99%
“…On the basis of previous publications, we defined a priori the following variables that might influence the variance in duration of action of cisatracurium and rocuronium: weight, 15,16 age, 17 sex, 18 ASA score, 19 blood loss, 20,21 lowest core body temperature, 22 duration of NBD administration, 23 and history of tobacco smoking. [24][25][26] Variables that correlated significantly (P = .15) with the mean dur 25 were included in our multiple regression analysis model, and an association of variables with the dur 25 of the respective NBD was assumed at a significance level of less than .05.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these NBDs are often used in anesthesia and intensive care medicine. 4 On the basis of published data, we thought that weight, 15,16 age, 17 sex, 18 American Society of Anesthesiologists (ASA) risk score, 19 blood loss (suggesting instability of cardiac output), 20,21 lowest core body temperature, 22 duration of NBD administration, 23 and tobacco smoking history [24][25][26] might contribute to the variance in the mean duration of action of cisatracurium and rocuronium.…”
mentioning
confidence: 99%
“…In this respect, benzylisoquinoline derivatives have an advantage over aminosteroids. Indeed, Arain et al [33] defined variability in the duration of neuromuscular block as the difference between its duration in a respective patient and the mean duration in the entire patient group. The duration of a neuromuscular blockade following the administration of vecuronium and rocuronium in patients over 60 years of age demonstrated a greater variability compared to cisatracurium.…”
Section: Benzylisoquinoline Derivativesmentioning
confidence: 99%